Pengaruh Variasi Bahan Pirolisis Menjadi Bahan Bakar Cair Berbasis Sampah Plastik PP dan PET - M.Rizqi Rosyadi Ahlis Suddin; Asroful Abidin; Mokh. Hairul Bahri (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2026)
This study aims to analyze the effect of variations in the composition of raw materials of Polypropylene (PP) and Polyethylene Terephthalate (PET) plastic waste on the characteristics of pyrolysis oil. The pyrolysis process was carried out using a batch-type reactor with a capacity of 2 kg at a constant temperature of 400°C with a residence time of 60 minutes, using variations of pure PP, pure PET, a mixture of 75% PP + 25% PET, and a mixture of 75% PET + 25% PP. The test results showed that the addition of PET fractions was linear with an increase in oil density values, where the highest density was obtained in pure PET at 0.994 g/mL and the lowest in pure PP at 0.964 g/mL. In contrast, the energetic performance and quantity of liquid products were dominated by the PP fraction; Pure PP oil produced the highest calorific value of 10,535.76 Cal/gram with a maximum liquid volume of 390 ml (yield 0.33%), while a mixture of 75% PET + 25% PP produced the lowest calorific value (8,266.82 Cal/gram) and the smallest oil volume of 280 ml (yield 0.29%). Therefore, the use of pure PP raw materials or a mixture dominated by PP is far superior and effective for producing alternative fuels with abundant quantities and high energy quality.